Evaluation of clinical and anatomical outcome of staged stenting after acute coiling of ruptured intracranial aneurysms. Issue 3 (June 2020) - Mine, Benjamin; Bonnet, Thomas; Vazquez-Suarez, Juan Carlos; Ligot, Noémie; Lubicz, Boris
Introduction: Stent-assisted coiling has widened indications and improved stability of endovascular treatment of intracranial aneurysms. However, stent-assisted coiling is usually not used to treat acutely ruptured intracranial aneurysms to avoid antiplatelet therapy. The objective of this study is to evaluate a strategy of staged endovascular treatment of ruptured intracranial aneurysms including coiling at the acute phase with complementary stenting with or without coiling at the subacute phase. Material and methods: Between 2012 and 2017, we retrospectively identified, in our prospectively maintained database, all patients treated for a ruptured intracranial aneurysm based on this staged stenting strategy. Clinical charts and imaging follow-up were analyzed to assess the procedural safety and feasibility as well as clinical and anatomical outcome. Results: We identified 23 patients with 23 intracranial aneurysms including 15 (65.2%) women with a mean age of 50 years (range 24–69 years). No rebleeding occurred during the mean delay of 24.3 days between initial coiling and stenting. All procedures were successful and additional coiling was performed in 5/23 procedures (21.7%). Clinical status was unchanged in all patients. At follow-up, the modified Rankin scale was graded 0 in 19/23 (82.6%), 1 in 2/23 (8.7%), and 2 in 2/23 (8.7%) patients, respectively. The rate of complete occlusion rose from 30.4% before the stenting procedure to 52.2% immediately after and 72.7% at follow-up. Conclusion: This strategy of early staged stenting in selected patients is safe and improves immediate intracranial aneurysm occlusion and long-term stability in this population at high risk of intracranial aneurysm recurrence with coiling alone.